APPLICATION OF THE NE BIS IN IDEM RELATED TO FINANCIAL OFFENCES IN THE JURISPRUDENCE OF THE EUROPEAN COURTS - Matić Bošković, Marina; Kostić, Jelena Ž. (NBP. Nauka, bezbednost, policija, 2020)
In the article, the authors analyze the fundamental challenges in the application of the ne bis in idem principle in the practice of the European Court for Human Rights and Court of Justice of the EU and their interpretation of the principle in relation to the application on the criminal offences and misdemeanour offences, including administrative penal offences, against the same person for the same acts. Article followed the development in interpretation of the principle by the European Court of Human Rights in Zolotukhin case to the interpretation of the Court of Justice of the EU in Menci case. European Courts jurisprudence could be used for dialogue on challenges that the Serbian judiciary and tax authories are facing in the interpretation of legislation and application of ne bis in idem principle on criminal and misdemeanour procedings against the same person for the same acts. The articile provides the basis for discussion on the unification of court practice.